A 26-Year-Old Woman With Diplopia and Nystagmus. Issue 4 (December 2020) - Anderson, William J.; Sharma, Aseem; Guzman, Miguel A.; Chung, Sophia M.
Abstract : Abstract: A 26-year-old woman presented for a routine contact lens evaluation but was found to have a subtle right sixth nerve paresis and adducting nystagmus of the left eye. She reported horizontal diplopia on far right gaze as well as subjective right-sided weakness and poor balance for 1 year. Brain and spinal MRI revealed multiple cystic lesions with variable enhancement throughout the posterior fossa and cervical spinal cord. These MRI findings were highly suspicious for an infectious central nervous system process, such as neurocysticercosis; however, primary or metastatic tumors were also important considerations. Tumor location and imaging characteristics were most helpful in differentiating among these etiologies. A brain biopsy ultimately established the diagnosis of a rosette-forming glioneuronal tumor.